(untitled) (Journal of Enam Medical College, 2024)
Background: Diabetes mellitus is a global problem. In diabetic subjects, blood glucose levels are elevated and HbA1c formation is increased. Estimation of HbA1c every two to three months is a measure of glycemic control. Blood lipid levels also undergo derangements in diabetic patients. Objective: We designed this cross-sectional study to explore any relationship of HbA1c with different blood lipids. Materials and Methods: This cross-sectional study was done in Bangladesh Institute of Health Sciences General Hospital during the period of January to December 2013. In this study 1253 type 2 diabetic subjects, both male and female, were included. Both male and female subjects were divided into three groups based on HbA1c levels. Total cholesterol, triglycerides and HDL-cholesterol levels of all subjects were measured by standard methods. LDL-cholesterol levels were calculated. All these parameters were compared among groups and their correlation with HbA1c was found. Results: Total cholesterol, triglycerides and LDL-cholesterol increased with increase in HbA1c% in both males and females; HDL-cholesterol showed no change in females, but in males it decreased with increase in HbA1c%. Conclusion: The findings of this study suggest that HbA1c% can be used as a biomarker of relative increase of total cholesterol, triglycerides and LDL-cholesterol in diabetic subjects. J Enam Med Col 2021; 11(3): 156-163